AN INTRODUCTORY OF PRODUCT INNOVATION AND MARKETING STRATEGY INTO SHELL WASTE-BASED SOUVENIR CRAFTS INDUSTRY IN THE CITY OF TANJUNG BALAI - Nurhayani, Ulfa; Azis, Adek Cerah Kurnia; Nasution, Akmal Huda; Herliani, Rini; Purba, Erni Luxy (Universitas Negeri Medan, 2018)
AbstractThe condition of the many shellfish wastes in Tanjung Balai City in North Sumatra Province makes a concern to the